TINJAUAN ULANG SALURAN IRIGASI KE NAGARIAN KOTO TANGAH KECEMATAN TILATANG KAMANG KABUPATEN AGAM - Aan Sagita Pratama; Surya Eka Priana; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2025)
The problem faced by the Kamang Magek irrigation canal, Tilatang District, Kamang, Agam Regency, is that the availability of water for community needs is not sufficient, because the water discharge is insufficient for needs and the channel dimensions are inadequate to irrigate rice fields with a channel length of 295 m and the area of the rice fields covered. flow 28.58 ha. This research aims to find out the causes of the lack of water capacity for the community's rice fields, as well as find out how to solve the problem.the results of this research are expected to be useful, including: Find out the water flow in the secondary channel, plan the dimensions of the secondary channel. From the evaluation of irrigation canals in Kamang Magek, Tilatang Kamang District, Agam Regency, the following data was obtained: the condition of the secondary irrigation channel in the irrigation area is in accordance with the calculation plan, so it is concluded that the channel is unable to hold water when rainfall is high.channel dimensions obtained from field calculations: width of channel dimensions = 120 m,water surface height = 0.20 mGuard height = 1 m.Based on the calculation, the Qmax value is smaller than the planned Q, so the irrigation channel is unable to accommodate water discharge that is higher than the maximum rainfall data.channel dimensions obtained from planning calculations: Channel dimension width = 0.4 m,Guard height = 1 m,Water surface height = 1.5 m.So based on the calculation the Qmax value is greater than Qplan, from the rainfall analysis it is clear that channel planning with large dimensions can accommodate maximum rainfall.